Biodiesel Production from Palm Oil with Heterogeneous Catalysts - Jonathan; Samuel Gidan Rumpaisum; Rif’an Fathoni (Journal of Green Chemical and Environmental Engineering, 2025)
Rice production in East Kalimantan Province during 2023 reached around 215,290 tons/year of milled dry grain. Rice is one of the main agricultural products that produce waste in the form of rice husks. Rice husk is stillNot well utilized so that it only becomes a pile of agricultural waste. Rice husk ash contains compounds that can be used as catalyst support, including SiO2. This study aims to determine the effect of rice husk ash catalyst from the KOH impregnation method as a catalyst for making biodiesel from conventional palm oil. Transesterification was conducted on palm oil with the ratio of catalyst mass to oil volume (10%, 15%, 20%). Biodiesel production from palm oil using KOH impregnated catalyst with 2N concentration and 20% catalyst concentration produced the highest yield of 86.3%. Viscosity and density of the results obtained meet the standards.